Covalently anchored ruthenium-phosphine complex on mesoporous organosilica: catalytic applications in hydrogenation reactions - Sisodiya, Sheetal; Lazar, Anish; Shylesh, Sankaranarayanapillai; Wang, Lei; Thiel, Werner R.; Singh, Anand Pal (Catalysis Communications, 2012)
New heterogeneous catalysts for alkene hydrogenation reactions were prepared by the immobilization of trimethoxysilane functionalized triphenylphosphine eta(6)-p-cymene ruthenium complex on mesoporous organosilica (PMO-Ru). Characterization techniques confirmed the structural integrity of the organosilica material and proved the successful anchoring of ruthenium complex. Catalytic activity and stability of PMO-Ru sample investigated in the hydrogenation of various olefins showed higher activity than a neat and MCM-41 supported ruthenium catalyst. High catalytic activity and stability of organosilica supported ruthenium catalyst are attributed to the hydrophobic environments and to the unique structural features imparted from the presence of organic groups in the framewall positions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Heterogenization; Hydrogenation; Organosilica; ruthenium; Triphenyl phosphine

Mn(III) based binapthyl schiff base complex hetrogenized over organo-modified SBA-15: synthesis, characterization and catalytic application - Sharma, Priti; Lazar, Anish; Singh, A. P. (Applied Catalysis A-General, 2012)
A heterogenized organocatalyst was synthesized by the covalent anchoring; of the complex chloro (S,S)(-)[N-3-tert-butyl-5-chloromethyl salicylidene]-N'-[3',5'-di-tert-butyl salicylidene] 1,1'-binapthyl-2,2'-diamine manganese(III) over modified mesoporous surface of SBA-15 through the reactive 3-aminopropyl trimethoxysilane (3-APTMS) group. The surface properties of the functionalized catalyst were analyzed by a series of characterization techniques such as elemental analysis, XRD, N-2 sorption measurement isotherm, FT-IR, TGA-DTA, XPS, and solid state C-13 NMR. The XRD and N-2 sorption measurement, UV reflectance and CP MAS NMR spectroscopy (C-13 and Si-29) of the catalyst confirmed the structural integrity of the mesoporous hosts and the spectroscopic characterization technique proved the successful anchoring of the metal complex over the modified mesoporous support. The screening of the catalyst Mn(III)-L-SBA-15 and neat Mn(III)-L complexes was done in the oxidation reaction of thioanisole (methyl phenyl sulfide) by using TBHP as an oxidant. Mn(III)-L-SBA-15 catalyst shows higher activities and turnover number (TON) and exhibit enhanced enantiomeric excess comparable to homogeneous catalyst [Mn(III)-L]. [Mn(III)-L-SBA-15] catalyst was found more active than homogeneous catalyst [Mn(III)-L]; Moreover bulkier alkene like 1,2-dihydronapthalene was also efficiently epoxidised with the synthesized supported catalyst. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Binaphthyl ligand; Chiral Schiff-base; Immobilization; Post grafting synthesis

Chiral (VO)-O-IV-Sal-Indanol complex over modified SBA-15: an efficient, reusable enantioselective catalyst for asymmetric sulfoxidation reaction - Lazar, Anish; Sharma, Priti; Singh, A. P. (Microporous and Mesoporous Materials, 2013)
A reusable, mesoporous, heterogeneous vanadium complex, (VO)-O-IV-Sal-Ind-SBA-15 has been synthesized first time from (1R,2S)-(+)-Cis-1-amino-2-indanol for enantioselective sulfoxidation reaction. The physico-chemical properties of the functionalized catalyst were analyzed by a series of characterization techniques like XRD, N-2 sorption measurement isotherm, TEM, FT-IR, XPS, EPR, DRS UV-Visible, ICP-OES and solid & liquid state C-13, Si-29 and V-51 NMR spectroscopy. Powder X-ray diffraction patterns, TEM and N-2 physisorption analysis confirmed the retention of mesoporous structure after various modifications. Solid-state NMR (C-13 CP-MAS NMR, Si-29 MAS NMR) and FT-IR analysis certified the integrity of organo-catalyst residing inside the pore channels of the mesoporous support. Further, XPS, EPR, V-51 NMR and DRS UV-Visible analyses help to find out the oxidation state and coordination environment of vanadium in (VO)-O-IV-Sal-Ind-SBA-15. Catalytic evaluation in asymmetric sulfoxidation reaction of sulfides indicated that VOIV-Sal-Ind-SBA-15 exhibited higher catalytic activity, stability, reusability and comparable enantioselectivity than SBA-15, PrNH2-SBA-15, neat (VO)-O-IV-Sal-Indanol complex and without catalyst. The effect of different catalysts, temperature, solvents and substrates on sulfoxidation reaction were examined in order to optimize the conversion and enantioselectivity of thioanisoles to sulfoxides. Crown Copyright (C) 2012 Published by Elsevier Inc. All rights reserved.
Keywords: (1R; 2S)-(+)-Cis-1-amino-2-indanol; Asymmetric sulfoxidation; Heterogeneous vanadium complex; Mesoporous; Thioanisole

Clay entrapped Cu(OH)(x) as an efficient heterogeneous catalyst for ipso-hydroxylation of arylboronic acids - Dar, Bashir Ahmad; Bhatti, Prince; Singh, A. P.; Lazar, Anish; Sharma, Parduman R.; Sharma, Meena; Singh, Baldev (Applied Catalysis A-General, 2013)
A remarkably active, selective and stable montmorilonite-KSF entrapped Cu(OH)(x) catalyst, has been prepared for the ipso-hydroxylation of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst shows excellent reusability without leaching and any significant loss in catalytic activity. The catalyst was characterized using, XRD, SEM, TPR, IR, XPS and BET surface area measurement techniques. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: clay; Copper; heterogeneous catalysis; Phenols; Water chemistry

Ultrasound promoted efficient and green protocol for the expeditious synthesis of 1, 4 disubstituted 1, 2, 3-triazoles using Cu(II) doped clay as catalyst - Dar, Bashir Ahmad; Bhowmik, Amrita; Sharma, Amit; Sharma, Parduman R.; Lazar, Anish; Singh, A. P.; Sharma, Meena; Singh, Baldev (Applied Clay Science, 2013)
Cu(II) doped clay catalyst has been prepared by an easy technique from inexpensive starting materials and investigated for the one pot synthesis of 1, 4-disubstituted 1, 2, 3-triazoles via Huisgen [3 + 2] cycloaddition under ultrasonic irradiation at room temperature. The catalyst is highly active, selective, and stable and can be reused several times. The prepared catalyst has been characterized by XRD, BET-SA, H-2-TPR, SEM and XPS techniques. This transformation is fast, efficient and does not require nitrogen atmosphere or anoxic conditions and additive. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Catalyst support; Copper catalyst; Crystallization; selectivity; Sustainability

Clay encapsulated Cu(OH)(x) promoted homocoupling of arylboronic acids: an efficient and eco-friendly protocol - Dar, Bashir Ahmad; Singh, Snehil; Pandey, Nalini; Singh, A. P.; Sharma, Priti; Lazar, Anish; Sharma, Meena; Vishwakarma, Ram A.; Singh, Baldev (Applied Catalysis A-General, 2014)
Cu(OH)(x) has been encapsulated over montmorillonite-KSF by simple ologomeric deposition strategy. The resulting catalyst has been employed for selective homocoupling of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst is easy to recover and shows excellent reusability without losing its activity. Techniques like XRD, SEM, TPR, IR, BET surface area measurement and XPS were used to characterize the catalyst. The present method promises for the simple and clean homocoupling of arylboronic acids. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biaryls; clay; Copper; Heterogenous catalyst; Homocoupling

Synthesis and characterization of 3-[N,N `-bis-3-(salicylidenamino)ethyltriamine] Mo(VI)O-2@SBA-15: a highly stable and reusable catalyst for epoxidation and sulfoxidation reactions - Lazar, Anish; Thiel, Werner R.; Singh, A. P. (RSC Advances, 2014)
The efficient and reusable oxidation catalyst 3-[N,N'-bis-3-(salicylidenamino)ethyltriamine] Mo(VI)O-2@SBA-15 has been synthesized by the anchoring of the 3-[N,N-bis-3-(salicylidenamino)ethyltriamine] ligand (L or Salpr) on the inner surfaces of organofunctionalized SBA-15 and subsequent complexation with Mo(VI) O-2(acac)(2). The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2-sorption measurements, TG & DTA, solid state C-13, Si-29 NMR spectroscopy, FT-IR, Raman spectroscopy, XPS, DRS UV-Vis spectroscopy, SEM and TEM. XRD and N-2 sorption analyses helped to find out the morphological and textural properties of the synthesized catalysts and confirm that an ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The (100), (110) and (200) reflections in SBA-15 provide hints of a good structural stability, the existence of long range ordering and a high pore wall thickness. TG and DTA results reveal that the thermal stability of (L)Mo(VI)O-2@SBA-15 was maintained up to 300 degrees C. The organic moieties anchored over the surface of the SBA-15 support were determined by solid state C-13 NMR and FT-IR spectroscopy. Further, solid state Si-29 NMR spectroscopy provides the information about the degree of functionalization of the surface silanol groups with the organic moiety. The electronic environment and the oxidation state of the molybdenum site in (L)Mo(VI)O-2@SBA-15 were monitored by Raman spectroscopy, XPS and DRS UV-Vis techniques. Moreover, the morphology and topographic information of the synthesized catalysts were confirmed by SEM and TEM imaging. The synthesized catalysts were evaluated in epoxidation and sulfoxidation reactions, and the results show that (L)Mo(VI)O-2@SBA-15 exhibits high conversion and selectivity towards epoxidation and sulfoxidation reactions in combination with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity. In addition, Sheldon's hot filtration test was also carried out.

Correlating the role of hydrophilic/hydrophobic nature of Rh(I) and Ru(II) supported organosilica/silica catalysts in organotransformation reactions - Lazar, Anish; George, Shoy C.; Jithesh, P. R.; Vinod, C. P.; Singh, A. P. (Applied Catalysis A-General, 2016)
Highly reactive and hydrophobic triphenyl phosphine based rhodium(I) and ruthenium(II) organometallic complexes over benzene containing periodic mesoporous organosilica (PMOB) have been synthesized. This has been achieved by the immobilization of neat metal complexes like RhCl(PPh3)(3) [Wilkinson catalyst], RuHCl(CO)(PPh3)(3) and RuCl2(PPh3)(3) over aminofunctionalized PMOB to get RhCl(PPh3)(2)-PrNH2PMOB, RuHCl(CO)(PPh3)(2)-PrNH2PMOB and RuCl2(PPh3)(3)-PrNH2PMOB, respectively. The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption analyses, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, SEM, TEM and contact angle measurements. The XRD and N-2 sorption analyses showed excellent textural properties with ordered mesoporous channel structure of all synthesized catalysts. The organic moieties anchored in PMOB were confirmed by C-13 CPMAS NMR and Fr-IR spectroscopy with Si-29 CPMAS NMR spectroscopy providing the information about the degree of functionalization of surface silanol groups with organic moiety. The Rh(I) and Ru(II) complexes supported on MCM-41/SBA-15/PMOE (ethane-PMO) were synthesized, and their catalytic activities in hydrogenation and sulfoxidation reactions were compared with Rh(I) and Ru(II) complexes supported on PMOB. The results show that PMOB based catalysts exhibit higher activities and selectivities than MCM-41/SBA-15/PMOB supported catalysts, neat homogeneous complexes and without catalyst. The better catalytic performance of PMOB based catalyst is attributed to the hydrophobic nature and high surface area of the PMOB support. The recycling studies of anchored catalysts show no major deactivation of the catalyst. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heterogeneous catalysts; Hydrogenation and sulfoxidation; Hydrophobic; Periodic mesoporous organosilica

Organofunctionalization of vanadium(III) acetylacetonate complex over aminofunctionalized SBA-15 for sulfoxidation reactions - Lazar, Anish; Sanjush, K. S.; Singh, A. P. (Advanced Porous Materials, 2016)
Recyclable SBA-15 supported aminopropyl vanadium(III) acetylacetonate heterogeneous catalyst has been synthesized by covalent anchoring of vanadium(III) acetylacetonate over aminofunctionalized SBA-15 via. post grafting method, V(III)(acac)3NH2@SBA-15. The synthesized catalyst was characterized by elemental analysis, ICP-OES, XRD, N2 sorption analysis, FT-IR, 29Si NMR spectroscopy, XPS, SEM and TEM. The percentage of nitrogen and vanadium in V(III)(acac)3NH2@SBA-15 was determined by elemental analysis and ICP-OES, respectively. XRD and N2 sorption analyses provide the information about the structural integrity (Mesoporous structure) and textural properties of all synthesized catalysts. The presence and degree of organofunctionalization on SBA-15 were monitored by FT-IR and 29Si NMR spectroscopy, respectively. Moreover, the oxidation state and the chemical environment of vanadium metal in V(III)(acac)3NH2@SBA-15 were revealed by XPS spectroscopy. Eventually, the morphology and topographic information of the synthesized catalysts were confirmed by SEM and TEM imaging. The synthesized catalyst was evaluated in oxidation of various sulfides and the results show that V(III)(acac)3NH2@SBA-15 catalyst exhibits higher conversion and selectivity towards the sulfoxidation reaction compared to the neat V(III)(acac)3 complex and blank reaction. The synthesized catalyst was recycled four times.

Phenylacetylene hydrogenation on Au@Ni bimetallic core-shell nanoparticles synthesized under mild conditions - Vysakh, A. B.; Lazar, Anish; Yadukiran, V.; Singh, A. P.; Vinod, C. P. (Catalysis Science & Technology, 2016)
The synthesis of Au@Ni bimetallic core-shell nanoparticles through an energy efficient (lower temperature) route in oleylamine following a sequential reduction strategy is reported. The method is found to be useful for the synthesis of a very thin nickel shell (2 nm) over a gold core (15 nm). Synergistic effects are observed in catalyzing phenylacetylene hydrogenation under different solvent conditions.

Simple, phosphine free, reusable Pd(II)-2,2 `-dihydroxybenzophenone-SBA-15 catalyst for arylation and hydrogenation reactions of alkenes - Lazar, Anish; Vinod, Chathakudath P.; Singh, Anand Pal (New Journal of Chemistry, 2016)
An efficient, simple, phosphine and co-catalyst free C-C coupling reaction heterogeneous catalyst via a post grafting method is developed and reported. A covalently anchored phosphine free Pd(II) based 2,2'-dihydroxybenzophenone (DHBP) complex over organofunctionalized SBA-15 has been synthesized by the reaction between aminofunctionalized SBA-15 (NH(2)SBA-15) and a 2,2'-dihydroxybenzophenone (DHBP) ligand, and further complexation with Pd(II)Cl-2 to get Pd(II)-DHBP@ SBA-15. The synthesized catalysts were characterized by elemental analysis, XRD, N-2 sorption analyses, TG, DTA, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. The synthesized catalysts were screened in arylation (Heck reactions) and hydrogenation reactions of alkenes, and the results show that Pd(II)-DHBP@ SBA-15 exhibits high conversion and selectivity towards arylation and hydrogenation reactions of alkenes with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity.

Synthesis of Au@Ni bimetallic core shell nanoparticle and nanochains in soyabean oil and their catalytic hydrogenation reactions - Bharathan, Vysakh A.; Yadukiran, V.; Lazar, Anish; Singh, Anand. P.; Vinod, Chathakudath P. (ChemistrySelect, 2016)
Synthesis of Au@Ni bimetallic core shell nanostructures using commercially available soya bean oil as the solvent through a sequential reduction strategy is reported. The energy efficiency and economic viability comes from the much milder temperatures and replacement of expensive and environmentally hazardous solvents like long chain organic amines and acids previously reported for synthesis. Thus, core shell nanoparticles having size regime of 10-15 nm with an excellent control over the nickel shell thickness (2 nm) over the gold core (8-10 nm) and Au@Ni nanochains is achieved. The synthesized materials are demonstrated to synergistically catalyze hydrogenation of nitro and C-C multiple bonds with much better efficiency as compared to individual nanoparticle counterparts.
Keywords: Bimetallic nanoparticles; Gold catalysis; hydrogenation reactions; synergistic effects

Exploration of amination reactions on highly extendable active sites of Pd(II)-3-allylsalicylaldiminophenol (ASIP) complex over thiofunctionalized SBA-15 - Lazar, Anish; Vinod, C. P.; Singh, A. P. (Microporous and Mesoporous Materials, 2017)
An effective and impressive heterogeneous catalyst, Pd(II)-3-allylsalicylaldiminophenol-SBA-15, dubbed as Pd(II)ASIP@SBA-15, for amination reactions of aryl halides to synthesize secondary amines (2), has been synthesized and characterized. Pd(II)ASIP@SBA-15 has been synthesized by the covalent anchoring of 3-allylsalicylaldehyde over thiofunctionalized SBA-15, then further reaction with 2-aminophenol, followed by metallation process by using Pd(11)(OAc)(2). A specifically designed cheap and easily available organic ligand, 3-allylsalicylaldiminophenol (ASIP), was synthesized from 3-allylsalicylaldehyde and 2-aminophenol. Using this, the synthesis of Pd(II)ASIP@SBA-15 was carried out whereby the ligand providing an active co-ordination or chelating sites for palladium metal. This strategy helped in exposing the Pd(11)ASIP active sites from surface to channels of SBA-15 support during the reactions. The synthesized catalyst were characterized by CHN analysis, PXRD, Nitrogen sorption analyses, TG & DTA, FTIR, C-13 and Si-29 CPMASS NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. Pd(II)ASIP@SBA-15 catalyst was screened in heterogeneous amination reactions of aryl halides to produce N-aryl derivatives or secondary amines with high catalytic activity as revealed by turn over frequency (TOF) calculations. To explore the heterogeneous nature of catalysts, amination reactions were carried with neat Pd(II)ASIP complex and Pd(11)(OAc)(2) catalysts. The catalyst was recycled several times without much loss of activity and Sheldon hot filtration test has been performed. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Amination Reactions; heterogeneous catalysis; Reusable; Supported catalysis

Heterogeneous route for transfer hydrogenation reactions of ketones using Ru(II)Cymene complex over modified benzene-organosilica (PMOB) - Lazar, Anish; Silpa, S.; Prabhakaran, Vinod C.; Singh, A. P. (Molecular Catalysis, 2017)
An inorganic-organic hybrid catalyst, Ru(II)Cym@PMOB, was synthesized by anchoring of [Ru(II)Cl-2(Pcymene)](2) complex which is derived from a reaction between hydrated ruthenium(III) trichloride and ocphellandrene over aminofunctionalized benzene-organosilica (PMOB). In the context of secondary alcohol synthesis from ketones, transfer hydrogenation (TH) reactions are convenient compared to conventional hydrogenation reactions owing to its lower activation energy and ambient pressure and mild temperature reaction" conditions. The synthesized catalysts were characterized by CHN analysis, XRD, ICP, N-2-sorption analysis, TG & DTA, FFIR,C-13 & 29Si solid NMR, UV-vis, TEM, SEM and XPS. The catalytic activities of neat [Ru(II)C-12(p-cymene)]2 complex and Ru(II)Cym@PMOB were evaluated in transfer hydrogenation (TH) of ketones (-97%) and compared with conventional hydrogenation reactions (-5%) where molecular H-2 was used. The results showed Ru(II)Cym@PMOB as highly active catalyst towards transfer hydrogenation (TH) reaction of acetophenones compared to neat [Ru(II)Cl-2(p-cymene)(12) complex. The heterogeneity of Ru(II)Cym@PMOB was confirmed by Sheldon's test. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Conventional Hydrogenation Reactions; Ru(II)Cym@PMOB; Transfer Hydrogenation Reaction; [Ru(II)Cl2(p-cymene)]2 complex

Distribution of water in the pores of periodic mesoporous organosilicates - a proton solid state MAS NMR study - Veena, V. S.; Illath, Kavya; Lazar, Anish; Vinod, C. P.; Ajithkumar, T. G.; Jayanthi, S. (Physical Chemistry Chemical Physics, 2018)
Solid state proton (H-1) magic angle spinning (MAS) NMR has been employed to study the distribution of confined water in ethane substituted periodic mesoporous organosilicate (PMOE) materials. Proton spectra acquired at different hydration levels are analysed and interpreted in terms of water clusters of various sizes and distributions of water layers on the pore surface. For comparison, we also performed similar experiments on SBA-15. The formation of larger clusters at lower hydration suggests that the pores of PMOE are getting filled with water at lower hydration levels than those in SBA-15. For PMOE, the simultaneous presence of two major resonances in the ranges 3.6-4.1 ppm and 4.4-5.2 ppm and their behaviour upon hydration imply a water layer distribution that is the sum of two contributions, corresponding to fully filled and partially filled pores or pore segments. Furthermore, the behaviour mentioned above suggests that both radial and axial filling mechanisms play a significant role in the hydration process. For SBA-15, as a function of hydration, we observed a smooth variation in the proton chemical shift of the main dynamic resonance. In accordance with previous studies, this is attributed to the gradual increase in the average thickness of water layers with an increase in hydration, and to a pore filling mechanism that is predominantly radial.

Highly selective aqueous phase hydrogenation of phenols over nanostructured RuO2 on MCM-41 catalysts - Betsy, K. J.; Lazar, Anish; Vinod, C. P. (Nano-Structures & Nano-Objects, 2018)
Selective aqueous phase hydrogenation of phenol as well as its derivatives is important for the synthesis of chemical intermediates which are crucial for the manufacture of high-tonnage commodities and a multitude of value added platform chemicals. Herein, we report a facile catalyst made of highly dispersed small RuO2 nanoparticles supported on mesoporous MCM-41 using one-pot approach. The optimal 5RuO2-MCM-41 catalyst with particle size 6-8 nm showed excellent activity and selectivity in aqueous phase hydrogenation of phenol and other functionalized substrates, which are building blocks of lignin, to corresponding cyclohexanol products without any additives. These catalysts showed better stability and can be reused several times without any significant drop in activity which proves the heterogeneity of the immobilized oxide catalyst.

Ru(II)-functionalized SBA-15 as highly chemoselective, acid free and sustainable heterogeneous catalyst for acetalization of aldehydes and ketones - Lazar, Anish; Betsy, K. J.; Vinod, C. P.; Singh, A. P. (Catalysis Communications, 2018)
Combining electron deficient Ru(II) coordination sites with organofunctionalized SBA-15, (L)Ru(Il)@SBA-15, result in a mild, neutral, water scavenger free and chemo-selective acetalization catalyst for cyclic/acyclic acetals. Vacant coordination sites of ruthenium in (L)Ru(II)@SBA-15 activates protecting groups as well as reactants simultaneously and restricts the reverse acetalization reaction. Synthesized (L)Ru(Il)@SBA-15 catalyst has been thoroughly characterized and act as competitive catalyst compared to conventional acid catalysts. (L) RuaD@SBA-15 performs high catalytic activity as well as selectivity within 20 min with high TOF. The catalyst can be recycled and reaction parameters are optimized.
Keywords: Acetalization reactions; Acid free; chemo-selective; heterogeneous catalyst; Reusable; Ru(II) immobilized SBA-15

Selective oxidation of cyclohexane to cyclohexanone using chromium oxide supported mesoporous MCM-41 nanospheres: probing the nature of catalytically active chromium sites - Betsy, Kurisingal J.; Nayak, Chandrani; Lazar, Anish; Krishnan, Athira; Bhattacharyya, Dibyendu; Jha, Shambhu N.; Vinod, Chathakudath P. (ChemCatChem, 2018)
Highly dispersed chromium oxide supported mesoporous MCM-41 nanosphere catalysts have been synthesized using a simple wet impregnation method. This work is devoted to a systematic study to reveal the active Cr sites in chromium oxide supported MCM-41 nanosphere catalysts for the selective oxidation of cyclohexane to cyclohexanone. To probe the nature of the active species, we synthesized 0.5-10wt% Cr loaded catalysts and characterized them by using XRD, UV/Vis spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, extended X-ray absorption fine structure analysis, X-ray absorption near edge structure analysis, N-2 sorption analysis, FTIR spectroscopy, (SiNMR)-Si-29 spectroscopy, SEM, and TEM. The liquid-phase oxidation of cyclohexane to cyclohexanone (99% selectivity) was performed under mild reaction conditions, and the results reveal clearly that the 5wt% Cr loaded catalyst was optimum for the reaction. The initial composition of isolated Cr3+ species in the catalyst is the major factor that influences the enhanced activity for cyclohexane oxidation.
Keywords: chromium; heterogeneous catalysis; Nanostructures; Oxidation; supported catalysts

CO2 hydrogenation to formate by palladium nanoparticles supported on N-incorporated periodic mesoporous organosilica - Betsy, K. J.; Lazar, Anish; Pavithran, Anjuna; Vinod, C. P. (ACS Sustainable Chemistry & Engineering, 2020)
Development of a heterogeneous catalyst capable of selective transformation of CO2 to valuable products still remains a challenge. In this article, we account for the surfactant-directed synthesis of a new framework-incorporated nitrogen-containing periodic mesoporous organosilica nanosphere (NPMO). A thoroughly characterized N-incorporated hybrid PMO was utilized as a platform for stabilizing well-dispersed and easily accessible Pd nanoparticles (Pd-NPMO) without using any stabilizing agents or expensive dendrimers. Further, this bifunctional hybrid catalyst has been demonstrated to heterogeneously catalyze aqueous phase CO2 hydrogenation (CO2/H-2 ratio 1:3) for the direct synthesis of formate under 4 MPa pressure and at 100 degrees C. To validate the superior performance of the Pd-NPMO catalyst, we compared the activity with Pd-SBA-15 catalysts, and the results showed a 10-fold increase in turnover frequency of 108 h(-1) using Pd on NPMO which envisaged the crucial role of nitrogen sites in this catalyst to boost the CO2 valorization to formate.
Keywords: CO2 hydrogenation; Formic acid synthesis; Hybrid silica; Pd nanoparticles; PMO

Pd nanoparticles supported on N-incorporated hybrid organosilica as an active and selective low-temperature phenol hydrogenation catalyst - Betsy, K. J.; Bajpai, Priyam; Lazar, Anish; Vanka, Kumar; Vinod, C. P. (ACS Applied Nano Materials, 2023)
A heterogeneous Pd-NPMO hybrid-silicacatalyst is synthesized andits application for aqueous phase selective hydrogenation of phenolto cyclohexanone at near ambient temperature (40 degrees C) and underatmospheric hydrogen pressure is demonstrated. The homogeneously distributedPd nanoparticles on N-bridged hybrid mesoporous organosilica showedremarkable activity and selectivity for cyclohexanone compared tothe unmodified Pd-SBA-15 catalyst. Control experiments strongly claimthe role of nitrogen domains in the organic framework of hybrid silicasupport in stabilizing small Pd nanoparticles and possibly modifyingthe Pd sites responsible for catalysis to activate the substrate moleculesin water. The hybrid silica catalyst was stable and reused severaltimes without any significant drop-in activity, proving the heterogeneityof the bifunctional Pd catalyst. Based on the density functional theorystudy and experimental interventions, a possible reaction mechanismfor the low-temperature phenol hydrogenation explaining the role oforganic domains in the hybrid-silica framework is proposed.
Keywords: cyclohexanone; Hybrid silica; palladium nanoparticles; Periodic mesoporous organosilica; phenol hydrogenation